2022
DOI: 10.1080/21645515.2022.2072138
|View full text |Cite
|
Sign up to set email alerts
|

Hope as a predictor for COVID-19 vaccine uptake in the US: a cross-sectional survey of 11,955 adults

Abstract: Widespread vaccine uptake is critical for ending the COVID-19 pandemic. As public health officials focus on overcoming vaccine hesitancy, simultaneously boosting hope may be equally important in the US. We analyzed data from an online cross-sectional survey conducted in June 2021. Participants were 11,955 US adults (ages 18–83) of various ethnicities, living in urban and rural settings. Of these, 71.3% had some college education. Mean age was 32.3 years and 72.4% reported being vaccinated against COVID-19. Mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Umucu et al [10] assessed vaccine hesitancy and uptake among 105 college students with disabilities, while adapting ten items of the VHS to COVID-19 without reporting the factor structure of the scale. Adam et al [11] conducted an online cross-sectional survey among 11,955 U.S. adults, while adapting 14 items of the VHS to COVID-19, without reporting the factor structure. Shen et al [12] assessed vaccine hesitancy associations among 2,361 Chinese adults, while adapting 10 items of the VHS to COVID-19 without assessing the scale’s association with actual vaccine uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Umucu et al [10] assessed vaccine hesitancy and uptake among 105 college students with disabilities, while adapting ten items of the VHS to COVID-19 without reporting the factor structure of the scale. Adam et al [11] conducted an online cross-sectional survey among 11,955 U.S. adults, while adapting 14 items of the VHS to COVID-19, without reporting the factor structure. Shen et al [12] assessed vaccine hesitancy associations among 2,361 Chinese adults, while adapting 10 items of the VHS to COVID-19 without assessing the scale’s association with actual vaccine uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Hope was even associated with willingness to get vaccinated. Adam et al 17 surveyed nearly 12,000 U.S. adults and found that hope was positively associated with vaccine uptake and confidence. Vaccine hesitancy, liberalized vaccine exemptions to maintain healthcare worker staffing, reported low community vaccination rates in some areas, and vaccine breakthrough were identified as sources for hope diminishment for IPs.…”
Section: Discussionmentioning
confidence: 99%